The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13045-019-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, a new form of cell death: opportunities and challenges in cancer

Abstract: Ferroptosis is a novel type of cell death with distinct properties and recognizing functions involved in physical conditions or various diseases including cancers. The fast-growing studies of ferroptosis in cancer have boosted a perspective for its usage in cancer therapeutics. Here, we review the current findings of ferroptosis regulation and especially focus on the function of ncRNAs in mediating the process of cell ferroptotic death and on how ferroptosis was in relation to other regulated cell deaths. Aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
838
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,161 publications
(922 citation statements)
references
References 112 publications
7
838
0
1
Order By: Relevance
“…Ferroptosis is a mode of programmed cell death that is characterized by an iron-dependent accumulation of lipid peroxides [48]. Interestingly, ferroptosis is considered to be pro-inflammatory and immunogenic, due to release of damage-associated molecular patterns (DAMPs) [67,68]. Hence, besides the direct effects on the tumor cells, artesunate may also support anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a mode of programmed cell death that is characterized by an iron-dependent accumulation of lipid peroxides [48]. Interestingly, ferroptosis is considered to be pro-inflammatory and immunogenic, due to release of damage-associated molecular patterns (DAMPs) [67,68]. Hence, besides the direct effects on the tumor cells, artesunate may also support anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial regulator of ferroptosis is the glutathione peroxidase 4 (GPX4), which neutralizes lipids derived from cellular metabolism, thus protecting the cells. The direct or indirect inhibition of GPX4 can cause ferroptosis that promotes the antitumor activity of some tumor suppressors (p53, PTEN, pRb) [68]. Even if cancer cells undergo a high oxidative stress maintaining a balanced level of iron, ferroptosis does not often happen in the cancer development.…”
Section: The Role Of Iron In Oxidative Stressmentioning
confidence: 99%
“…The ROS-and iron-overload cell death became a new target of therapeutic strategy in several disease, including cancer. Indeed, it has been shown that some ferroptosis-inducing agents, such as erastin or sorafenib, have anti-tumor activity [68].…”
Section: The Role Of Iron In Oxidative Stressmentioning
confidence: 99%
“…Emerging evidence indicated that ferroptosis might be an adaptive process to remove carcinogenic cells [7, 8]. Several modulators of ferroptosis have been linked to certain tumors [9]. Glutathioneperoxidase-4 acts as a key antioxidant in redox regulation, and is a regulator of ferroptosis [10, 11].…”
Section: Introductionmentioning
confidence: 99%